Evaluation of US prescription patterns: Are treatment guidelines for cancer-associated venous thromboembolism being followed?. Issue 145 (September 2016) - Khorana, Alok A.; Yannicelli, Daniel; McCrae, Keith R.; Milentijevic, Dejan; Crivera, Concetta; Nelson, Winnie W.; Schein, Jeffrey R.
Abstract: Introduction: Venous thromboembolism (VTE) is a common complication of cancer. Clinical practice guidelines recommend low-molecular-weight heparin (LMWH) for treatment of cancer-associated VTE, but it is unclear how frequently these are followed. This study assessed anticoagulation treatment patterns for VTE in newly diagnosed cancer patients in the United States. Materials and methods: MarketScan® claims records of more than 80 million insured members between January 1, 2009 and July 31, 2014 were retrospectively analyzed. Subjects were included if they were 18 years of age or older, and had a diagnosis of cancer (9 solid tumor types) and VTE. Data were included for LMWH, warfarin, and other anticoagulants (fondaparinux and direct oral anticoagulants [DOACs]). Patients with anticoagulant treatment prior to cancer diagnosis were excluded. Results: VTE developed in 6.2% of cancer patients (median, 181 days after cancer diagnosis). VTE rates were highest for pancreatic (17.5%) and lung (12.6%) cancer and lowest for breast (4.2%) and prostate (4.1%) cancer. For patients for whom outpatient prescription data were available, warfarin was most commonly used (50.0%), followed by LMWH (40.0%) and other anticoagulants (10.0%). Over 6 months, 13% of patients who initiated injectable anticoagulants remained on them compared with 30% of those who initiated oral anticoagulants. More patients switched from LMWH to warfarin and other anticoagulants (44%) versus those who switched from warfarin (28%). Conclusions: Warfarin was the most utilized anticoagulant for cancer-associated VTE despite guideline recommendations for LMWH. More patients remained on oral versus injectable agents, which may be related to self-injection burden and costs.